PROBLEMATICS OF LAW ENFORCEMENT OF UNION BUSTING CRIMINAL ACTION IN GORONTALO PROVINCE - Rais, Suardi (Jurnal Hukum Volkgeist, 2020)
Although freedom of association has been more than a decade old, workers in Indonesia still face enormous challenges in exercising their collective rights. this is inseparable from the problem of law enforcement against anti-union / labor crime. This study aims to explain and analyze how the form of legal protection of trade unions in Law No. 21 of 2000 concerning Trade Unions / Trade Unions and what are the barriers to law enforcement in the imposition of criminal sanctions against union busting perpetrators in Gorontal Province. The method used in this study is a merger between normative research and empirical research methods. The results of this study indicate that the form of protection and law enforcement against violations or criminal acts against the union that occurred especially in the Province of Gorntalo is still very weak, there has been no decisive action from all law enforcement. The workings of the law are inseparable from the law enforcers themselves, law enforcement against criminal acts of the Anti Trade union basically still encounters several obstacles among which are understanding concepts among law enforcers of Law No.21 of 2000 concerning Trade Unions / Labor Unions and lack of coordination among PPNS Employment investigators and Police Investigators.